Supporting Girls' Engineering Habits of Mind With STEM Education - Erol, Ahmet; Erol, Mustafa; Erol, Merve Canbeldek (WILEY, 2025)
STEM is a field where gender stereotypes regarding men persist. Women are underrepresented compared to men in STEM fields. The social belief that engineering is only for men discourages young girls from pursuing such endeavors. Encouraging young girls to enter STEM fields is crucial to dispel these stereotypes. Therefore, one of the essential aspects of beginning STEM education in early childhood is dismantling the gendered perception of professions. This study aimed to support girls' engineering habits of mind (EHoM) with STEM education. The participants in the study were eight 5-year-old children. Children participated in six STEM activities for 12 weeks. Two days per week and 120 min per day were devoted to practice. We collected the data using the observation protocol, interview protocol, and reflective diary and analyzed it using content analysis. We explained the results within the context of six fundamental EHoM mentioned previously in the literature: systems thinking, creativity, optimism, collaboration, communication, and attention to ethical considerations. While collaboration, communication, systems thinking, and creativity were the most utilized habits of mind in STEM education, attention to ethical considerations was the least used. The girls found numerous opportunities to support their EHoM in this process. Our findings indicate that STEM education can help girls' EHoM.
Keywords: Early STEM education; engineering habits of mind; gender; girls; SCIENCE; THINKING; Psychology